Contribution to the development of the Forest Stewardship Council Policy on Conversion - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
FTA contributed to the development of the policy which provides FSC’s general position and fundamental principles on conversion of natural forests and High Conservation Value areas to other land uses.